Paralympic sport performance: How can diversity in training, equipment, ergonomics and impairment result in fair competition? - Vanlandewijck, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Since the first International Wheelchair Games held in 1948 at Stoke Mandeville Hospital in England major changes have occurred in Paralympic sports. While the events in the early days were more about enhancing the quality of life for people with spinal cord injuries, they have now evolved into elite-level competitive games for athletes with a diversity of impairments. The wheelchairs used have transformed from heavy, bulky, one-size-fits-all hospital chairs used for all events into light-weight, fast, custom-fit chairs specially made for each sports discipline. Analogously, the competitor has transformed from a rather untrained, unfit patient with a disability into a highly trained, fit, often full-time, professional athlete. This lecture explains how diversity threatens fairness in competition and frames the way the International Paralympic Committee is anticipating.